La contabilidad gubernamental y la gestión logística en la Municipalidad Distrital de San Juan Bautista en el periodo 2022 - Alegria Cachique, Alfredo (2024)
The research addresses relevant aspects of government accounting and logistics management, elaborated through a quantitative, descriptive and correlation approach, with a non-experimental design, with 135 workers being the population whose main objective was to determine the relationship between government accounting and logistics management in the district municipality of San Juan Bautista, in the period 2022. The investigation has determined that Government Accounting is mostly Good at 54.46%, followed by Regular with 42.57%, and finally Bad with 2.97%, Likewise, Logistics Management is mostly Good at 63.37%, Regular at 34.65%, and finally Bad at 1.98%. On the other hand, the Correlation Coefficient between Government Accounting and Logistics Management was identified equal to Rho=0.736 and the value Sig. (bilateral)=0.000; Therefore, it is concluded that there is a high positive relationship between government accounting and logistics management in the district municipality of San Juan Bautista, in the period 2022.